Risk and Protective Correlates of Young Women's First Sexual Experiences in Rakai, Uganda. - Mmari, Kristin N.; Kaggwa, Esther; Wagman, Jennifer; Gray, Ron; Wawer, Maria; Nalugoda, Fred (International Perspectives on Sexual & Reproductive Health, 2013)
CONTEXT: Sexually active young women bear the brunt of the HIV epidemic in Sub-Saharan Africa. Information is needed on risk and protective correlates at the family, partner and individual level for the design of programs to encourage safer sexual behaviors and reduce HIV risk among young women. METHODS: The study was conducted among 1,675 sexually experienced women aged 15-24 living in Rakai, Uganda. The sample was taken from an ongoing community cohort study initiated in 1994 in 56 villages by the Rakai Health Sciences Program. Contextual variables at the family, partner and individual levels were analyzed in relation to three outcome variables: sex before the age of 15, coerced first sex and condom use at first sex. RESULTS: At the family level,young females who did not live with both parents were more likely than those who did to have had sex before the age of 15 and to have experienced sexual coercion at first sex. Those whose mothers had some secondary education and whose female caregiver did not consume alcohol had elevated odds of using a condom at first sex. Having initiated sex at age 15 or older was the strongest individual-level characteristic associated with having used a condom at first sex. CONCLUSIONS: Reproductive health interventions should target adolescents and their parents to delay the onset of sexual activity, prevent sexual coercion and encourage condom use. Both adolescents and their parents should be educated about the risks associated with different types of sexual partnerships.